Influence of the first wall material on the particle fuelling in ASDEX Upgrade. (3rd April 2017) - Lunt, T; Reimold, F; Wolfrum, E; Carralero, D; Feng, Y; Schmid, K
Abstract: In the period from 2002 to 2007 the material of the plasma facing components (PFCs) of ASDEX Upgrade (AUG) was changed from carbon (C) to tungsten (W). Comparing the measured density profiles of low-density L-mode discharges with little or no gas puff before and after this modification, a significantly higher pedestal-top density was found for W PFCs together with a steeper gradient and a lower pedestal temperature. This change can be explained by larger particle- and energy reflection coefficients for D on W compared to D on C, as shown by EMC3-EIRENE simulations of AUG discharges in similar conditions on a computational grid extending to the main chamber first wall. In the simulations, a change of the wall material at fixed separatrix density indeed shows that for W PFCs more neutrals cross the separatrix, resulting in a steeper density gradient. Analysis of the source resolved and poloidally resolved neutral flux densities across the separatrix show a dominant contribution of the divertor targets to the fuelling profile in the simulation of the low density case. Increasing the density decreases the electron temperature at the target and therefore the potential drop in the electrostatic sheath as well as the energy of the ions impinging on the surface. Neutrals with ∼eV energies, able to reach the separatrix, are then only produced via molecular dissociation processes in the plasma volume independently of the PFC material. Also the contribution of the main chamber PFCs to the fuelling is observed to increase at higher densities.